COVID-19-related clinical outcomes among Korean hemodialysis patients - Hayne Cho Park; Young-Ki Lee; Eunsil Ko; Sungbong Yu; AJin Cho; Do Hyoung Kim; Jinseog Kim; Jang-Hee Cho; Jeonghwan Lee; Dong Ki Kim; Seong Nam Kim; Chul-Woo Yang (The Korean Society of Nephrology, 2022)
Background Hemodialysis (HD) patients are more vulnerable to viral epidemics, experiencing higher mortality rates compared to individuals without chronic kidney disease (CKD). This retrospective cohort study sought to demonstrate clinical outcomes and associated factors among coronavirus disease 2019 (COVID-19) confirmed Korean HD patients. Methods From February 2020 to November 2021, the COVID-19 Task Force Team collected clinical data for HD patients with confirmed COVID-19 via a self-report survey of nephrologists. The composite outcome included in-hospital mortality, admission to the intensive care unit (ICU), and use of mechanical ventilation. Risk factors associated with clinical outcomes were analyzed among HD patients and compared to those of individuals without CKD using the COVID-19 database from the Korea Disease Control and Prevention Agency. Results A total of 380 HD patients from 206 facilities were diagnosed with COVID-19. Fever (49.5%) and cough (25.7%) were the two most common initial symptoms. The overall in-hospital fatality rate was 22.4% and even higher among ICU admission cases (64.7%). Non-survivors were older, more frequently developed shortness of breath, and were more likely to come from a nursing hospital. Compared to the age- and sex-matched non-CKD population, HD patients showed greater risk of in-hospital mortality (hazard ratio, 2.07; 95% confidence interval, 1.56-2.75; p < 0.001) and composite outcome (hazard ratio, 3.50; 95% confidence interval, 2.56-4.77; p < 0.001). Conclusion HD patients have a greater risk of in-hospital mortality and morbidity from COVID-19. Special attention should be paid to COVID-19 HD patients when they are older or present with symptoms.